2012
DOI: 10.1080/15555240.2012.666463
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Bully? Bullying Behavior and Its Implication on the Bullied

Abstract: This study examined the causes that lead to the development of workplace bullying behavior and its subsequent implication on the bullied employee in the Indian organizational context. It also attempted to shed some light into the prevailing culture in the Indian organizations that influence workplace bullying in a sample of 24 employees associated with three different companies. Qualitative methods were used to collect the data via in-depth interviews. During the discussion, four main causes leading to workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Dhar's research revealed several reasons and people who have the potential to carry out bullying, [23] Economic status. Poverty status is found to be a high risk factor for being a victim of violence in his community.…”
Section: A Psychological Perspective On Bullying Behaviormentioning
confidence: 99%
“…Dhar's research revealed several reasons and people who have the potential to carry out bullying, [23] Economic status. Poverty status is found to be a high risk factor for being a victim of violence in his community.…”
Section: A Psychological Perspective On Bullying Behaviormentioning
confidence: 99%
“…31 Bullying verbal. Bullying verbal yaitu, seperti memfitnah, pencemaran nama baik, menahan informasi, menghina, mengucilkan korban dari teman sebaya, mengabaikan pendapat dan lain (Dhar, 2012), menyebut nama/ejekan Nansel et al, 2001), mengancam (Nansel et al, 2001), menggoda Dhar, 2012), dan lain sebagainya. Secara nyata, bullying verbal sangat mempengaruhi citra diri seseorang dan juga mempengaruhi emosional dan psikologis korban bullying.…”
Section: Jenis-jenis Bullyingunclassified
“…Triggers for workplace bullying are not thoroughly comprehended (Dhar, 2012). More specifically, individual precursors to this behaviour have been less broadly examined than organizational factors (Francioli et al 2016 citing Glaso, Nielsen, & Einarsen, 2009).…”
Section: Workplace Bullying and Neurodiverse Employeesmentioning
confidence: 99%